Cytoskeletal proteins in the follicular wall of normal andcystic ovaries of sows - de Sant´Ana, Fabiano J.F. (2015)
The expression of cytoskeletal proteins was evaluated immunohistochemically in 36 normal ovaries sampled from 18 sows and 44 cystic ovaries sampled from of 22 sows, was evaluated. All sows had history of reproductive problems, such as infertility or subfertility. The immunohistochemically stained area (IHCSA) was quantified through image analysis to evaluate the expression of these proteins in the follicular wall of secondary, tertiary, and cystic follicles. Cytokeratins (CK) immunoreactivity was strong in the granulosa cell layer (GC) and mild in the theca interna (TI) and externa (TE) of the normal follicles. There was severe reduction of the reaction to CK in the GC in the cystic follicles, mainly in the luteinized cysts. The immunoreactivity for vimentin was higher in the GC from normal and cystic follicles in contrast with the other follicular structures. In the luteinized cysts, the IHCSA for vimentin was significantly higher in TI and in both observed cysts, the labeling was more accentuated in TE. Immunohistochemical detection of desmin and α-SMA was restricted to the TE, without differences between the normal and cystic follicles. The results of the current study show that the development of ovarian cysts in sows is associated to changes in the expression of the cytoskeletal proteins CK and vimentin.